2022
DOI: 10.1101/2022.10.16.22281153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High levels of serum cholesterol positively correlate with the risk of the development of vessel co-opting tumours in colorectal cancer liver metastases

Abstract: Colorectal cancer liver metastatic (CRCLM) tumours present as two main histopathological growth patterns (HGPs) including desmoplastic HGP (DHGP) and replacement HGP (RHGP). The DHGP tumours obtain their blood supply by sprouting angiogenesis, whereas the RHGP tumours utilize an alternative vascularisation known as vessel co-option. In vessel co-option, the cancer cells hijack the mature sinusoidal vessels to obtain blood supply. Vessel co-option has been reported as an acquired mechanism of resistance to anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…The RHGP tumours are characterized by vessel co-option vascularization and the patients with RHGP tumours have the worse prognosis compared to their counterparts as demonstrated in this manuscript and previous publications 27,39 . Since RHGP tumours do not utilize angiogenesis, the tumours are resistant to anti-angiogenic agents, such as Bevacizumab 15,27 .…”
Section: Discussionsupporting
confidence: 72%
“…The RHGP tumours are characterized by vessel co-option vascularization and the patients with RHGP tumours have the worse prognosis compared to their counterparts as demonstrated in this manuscript and previous publications 27,39 . Since RHGP tumours do not utilize angiogenesis, the tumours are resistant to anti-angiogenic agents, such as Bevacizumab 15,27 .…”
Section: Discussionsupporting
confidence: 72%
“…It has been reported that metformin reduces the serum levels of low-density lipoprotein cholesterol (LDL-C) by suppressing the transcription of proprotein convertase subtilisin/kexin type 9 (PCSK9) [ 61 ]. Importantly, we previously showed upregulation of PCSK9 in the liver parenchyma of vessel co-opting CRCLM specimens [ 62 ]. Moreover, our preclinical data suggested that using hypocholesterolemic drugs, including anti-PCSK9 (Evolocumab), significantly attenuates the development of vessel co-opting CRCLM tumours [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we previously showed upregulation of PCSK9 in the liver parenchyma of vessel co-opting CRCLM specimens [ 62 ]. Moreover, our preclinical data suggested that using hypocholesterolemic drugs, including anti-PCSK9 (Evolocumab), significantly attenuates the development of vessel co-opting CRCLM tumours [ 62 ]. Therefore, we postulate that metformin may also affect the generation of vessel co-option tumours in CRCLM via regulation of PCSK9 and LDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…We performed immunohistochemical staining for formalin-fixed paraffin-embedded (FFPE) specimens as described in previous publications (24,25). We performed staining using RUNX1 antibody 1:200 (LS Bio, #LS-C353932).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…We previously reported that treating tumours with evolocumab attenuates the generation of vessel co-opting tumours in CRCLM (25). However, the role of evolocumab in increasing the efficacy of anti-angiogenic (anti-VEGF) therapy in CRCLM is unclear.…”
Section: Treatment With Evolocumab Increases the Efficacy Of Anti-ang...mentioning
confidence: 99%